2015
DOI: 10.1523/jneurosci.1339-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal RARβ Signaling Modulates PTEN Activity Directly in Neurons and via Exosome Transfer in Astrocytes to Prevent Glial Scar Formation and Induce Spinal Cord Regeneration

Abstract: Failure of axonal regeneration in the central nervous system (CNS) is mainly attributed to a lack of intrinsic neuronal growth programs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 45 publications
6
72
0
2
Order By: Relevance
“…In a rat model of cervical dorsal root avulsion (C5–T1), the newly developed RARbeta agonist was given (23). After 4 weeks of treatment, behavioral tests showed recovery of sensory (the sticky tape test; sensing and removal) and locomotor function (the horizontal ladder test).…”
Section: Adjuvant Therapy For Spinal Cord Sensory Regenerationmentioning
confidence: 99%
“…In a rat model of cervical dorsal root avulsion (C5–T1), the newly developed RARbeta agonist was given (23). After 4 weeks of treatment, behavioral tests showed recovery of sensory (the sticky tape test; sensing and removal) and locomotor function (the horizontal ladder test).…”
Section: Adjuvant Therapy For Spinal Cord Sensory Regenerationmentioning
confidence: 99%
“…In this regard, conflicting evidence exists over the importance of scar tissue as a barrier for axonal growth. A number of reports supporting the role of scar tissue as a barrier have shown that its removal facilitates neural restoration [1618]. However, recent studies have also suggested that scar tissue is not necessarily an obstacle for regeneration and may even be necessary for neural restoration [19].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, exosomes released by neurons contain alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors, while exosomes secreted from neurites of depolarized neurons are enriched with microtubuleassociated protein 1b (MAP1b) and miRNAs that target genes involved in neurite plasticity (86,87). Exosomes from neurons treated with a retinoic acid receptor β2 (RARβ) agonist had a dual effect on neurons and astrocytes to inactivate PTEN signaling, leading to enhancement of neurite outgrowth (88). RARβ agonist inactivated cortical neuron PTEN signaling by releasing exosomes enriched with PTEN.…”
Section: Exosomes and Neuronal Plasticitymentioning
confidence: 99%
“…RARβ agonist inactivated cortical neuron PTEN signaling by releasing exosomes enriched with PTEN. These PTEN-enriched neuronal exosomes transferred PTEN proteins into astrocytes to suppress astrocyte proliferation (88). In addition to neurons, exosomes released by cortical neurons transferred miR-124 to astrocytes and increased the expression of the excitatory amino acid transporter GLT-1 in astrocytes, suggesting a role for neuronal exosomes in regulatIn addition, activation of the Notch signaling pathway between cerebral endothelial cells and pericytes is required for cerebral angiogenesis and BBB integrity (72).…”
Section: Exosomes and Neuronal Plasticitymentioning
confidence: 99%